Association between serum oestradiol level on the hCG administration day and neonatal birthweight after IVF-ET among 3659 singleton live births - Yu Liu (Nature Portfolio, 2021)
Abstract Oestradiol, an important hormone in follicular development and endometrial receptivity, is closely related to clinical outcomes of fresh in vitro fertilization-embryo transfer (IVF-ET) cycles. A supraphysiologic E2 level is inevitable during controlled ovarian hyper-stimulation (COH), and its effect on the outcome of IVF-ET is controversial. The aim of this retrospective study is to evaluate the association between elevated serum oestradiol (E2) levels on the day of human chorionic gonadotrophin (hCG) administration and neonatal birthweight after IVF-ET cycles. The data of 3659 infertile patients with fresh IVF-ET cycles were analysed retrospectively between August 2009 and February 2017 in First Hospital of Zhengzhou University. Patients were categorized by serum E2 levels on the day of hCG administration into six groups: group 1 (serum E2 levels ≤ 1000 pg/mL, n = 230), group 2 (serum E2 levels between 1001 and 2000 pg/mL, n = 524), group 3 (serum E2 levels between 2001 and 3000 pg/mL, n = 783), group 4 (serum E2 levels between 3001 and 4000 pg/mL, n = 721), group 5 (serum E2 levels between 4001 and 5000 pg/mL, n = 548 ), and group 6 (serum E2 levels > 5000 pg/mL, n = 852). Univariate linear regression was used to evaluate the independent correlation between each factor and outcome index. Multiple logistic regression was used to adjust for confounding factors. The LBW rates were as follows: 3.0% (group 1), 2.9% (group 2), 1.9% (group 3), 2.9% (group 4), 2.9% (group 5), and 2.0% (group 6) (P = 0.629), respectively. There were no statistically significant differences in the incidences of neonatal LBW among the six groups. We did not detect an association between peak serum E2 level during ovarian stimulation and neonatal birthweight after IVF-ET. The results of this retrospective cohort study showed that serum E2 peak levels during ovarian stimulation were not associated with birth weight during IVF cycles. In addition, no association was found between higher E2 levels and increased LBW risk. Our observations suggest that the hyper-oestrogenic milieu during COS does not seem to have adverse effects on the birthweight of offspring after IVF. Although this study provides some reference, the obstetric-related factors were not included due to historical reasons. The impact of the high estrogen environment during COS on the birth weight of IVF offspring still needs future research.